Antimicrobial effect of aqueous extracts from the peel, pulp and grape seed (vitis vinifera) on Streptococcus mutans, in vitro study - Caicedo Salazar, Josué (2018)
Objective: To determine the antibacterial activity of aqueous grape extracts (Vitis vinifera) obtained from the skin, seed and pulp, on Streptococcus mutans (ATCC 35668, Ecuador), using 0.12% chlorhexidine as a positive control and distilled water as a negative control. Materials and methods: Aqueous extracts were obtained from the pulp, seeds and grape skin of the northern region of Ecuador, at a concentration of 40, 70 and 100%, which were impregnated 20 ml each in paper filter discs. and placed in Petri dishes with strains of Streptococcus mutans inoculated on blood agar, disks impregnated in 0.12% chlorhexidine and distilled water were used as control; the antimicrobial activity was evaluated considering the inhibition zones obtained at 24 and 48 hours of incubation. Results: The evaluation times 24 and 48 were different (p = 0.00) showing a greater inhibitory effect at 48 hours, where the 100% grape seed extract presented antimicrobial activity similar to 0.12% chlorhexidine, and the 70% concentration of the same extract reduced inhibition. However, peel and pulp extracts in their different concentration did not present halos of inhibition against Streptococcus mutans. Conclusions: The aqueous extract of 100% grape seeds showed antimicrobial activity similar to 0.12% chlorhexidine against Streptococcus mutans.